PENGARUH BUDAYA ORGANISASI DAN PENGEMBANGAN KARIR TERHADAP KINERJA PEGAWAI PADA KANTOR PELAYANAN PAJAK PRATAMA SURABAYA WONOCOLO. - Vivi Kurniawati; Pompong Budi Setiadi (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
In an organization or company, Human Resource Management (HRM) is one element that has a strategic function that supports the success of an organization or company to achieve its goals. The influence of organizational culture and career development in its function, namely managing human resources and providing facilities to these employees in a company will affect employee work behavior which in turn will affect the overall performance of a company. The purpose of this study is to determine the effect of organizational culture on employee performance and the influence of career development on employee performance at the Surabaya Wonocolo Tax Service Office. The instrument of this research used a questionnaire. Samples were taken as many as 50 respondents, employees of the Surabaya Wonocolo Tax Service Office. Analysis and data processing using SPSS. The results of this study indicate that organizational culture has no effect on employee performance, while career development has an effect on employee performance.